Technology support for the inclusion of deaf students in mainstream schools: a summary of research from 2007 to 2017 - Constantinou, Vaso; Ioannou, Andri; Klironomos, Iosif; Antona, Margherita; Stephanidis, Constantine (My University, 2020)
The paper examines the use of technology as a means for the inclusion of Deaf and Hard of Hearing (DHH) students in mainstream K-12 schools, covering the publications of the last decade. A systematic search of databases was carried out to locate theoretical and empirical studies investigating technologies as auxiliary or supporting tools for the inclusion of DHH students. Results are presented in two categories: (1) review/survey or theoretical papers and (2) studies of technology design and evaluation. Based on our findings, there is only preliminary evidence on how technology can support the inclusion of DHH students in mainstream schools. We argue that there is less need for research on technologies specialized on the disability, aiming to accommodate hearing loss, such as technologies to support the acquisition of sign language or speech-to-text translation of the teacher’s talk. There is a major need for technology integration and research on its real-world use and utility, towards the inclusion of all students in the mainstream classroom, serving the needs of both DHH students and the general student population.
Keywords: Deaf; Hard of hearing; Hearing impaired; Inclusion; Mainstream education; Technology-enhanced learning